KEWIRAUSAHAAN SOSIAL SEBAGAI PILAR MEMBANGUN EKONOMI MASYARAKAT - Anita Apriani; Windy Jatmika, Muhtar Syam (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to explore the role of social entrepreneurship as a measure of the success of economic development. In the current era of globalization, the country’s development is very dependent on the economic sector which is a factor in the success realized by the government. Entrepreneurship makes the role of the community an important element for national development, specifically economic developzed by the government. Entrepreneurship makes the role of the community an important element for national development, specifically economic development. This research seeks to describe the role and position of social entrepreneurship as a driving force in the national economy which has a strategic function in forming long-term businesses. The condition in very possible because the position of social entrepreneurship in quite influential in the Indonesian economy. The research method uses document studies obtained through the use of internet-based technology of things and relevant books. The conclusion concludes that social entrepreneurship is proven to have a strong position in achieving economic development by looking at various programs from the government titled asisting the social entrepreneurship practice movement targeting the poor who participate